2011
DOI: 10.1111/j.1365-2591.2011.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracanal dentine wettability on human dental pulp cell attachment

Abstract: Surface wettability was affected by the irrigants. Increasing in wettability produced higher levels of HDPC attachment to irrigated dentine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
1
22
1
4
Order By: Relevance
“…, Huang et al . ), so it is also very likely that bubble entrapment was favoured. This study also reported the entrapment of large bubbles in the apical part of the root canal.…”
Section: Discussionmentioning
confidence: 99%
“…, Huang et al . ), so it is also very likely that bubble entrapment was favoured. This study also reported the entrapment of large bubbles in the apical part of the root canal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the induced bleeding step in regenerative procedures was found to convey a significant amount of stem cells into the canal space (9). The wettability of radicular dentin was suggested to modify the attachment of dental pulp cells to dentin (10). Furthermore, increase in surface wettability of a substrate was associated with significant improvement in cellular attachment and protein adsorption (11).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the chemical composition of the dentin after root canal irrigation can affect the viability of cells seeded onto the surface of the dentin (31,32) and therefore should be of concern in pulp regenerative treatment. Increased intensities of Na + (23u) and Cl À (35 and 37u), which were NaOCl breakdown products (4) observed after irrigation with NaOCl, could be accountable for the reduced viability of cells (31,32). It was also possible that the residual layer of CHX noted in the current study could create an unfavorable environment for cell viability and cell adhesion (31).…”
Section: Discussionmentioning
confidence: 99%
“…The information obtained from this study will be crucial to understand the effect of chemicals on dentin surface (14,15,29) and their role in bonding, sealing (30), cell adhesion, and healing potential of endodontic therapy (31,32).…”
mentioning
confidence: 99%